Analysis of Aspect Extraction Methods in Regular Opinions - Vieira, João Paulo Albuquerque (2020)
This work presents a comparative analysis between the main approaches used at the task of Extraction of Aspects in reports about products and services on web sites. Adaptations of four methods of extraction of aspects were implemented and evaluated using two distinct Corpora, one in Portuguese and another in English. On the experiments performed it was observed that the approach using supervised learning (convolutional neural networks) obtained better results on the others.